2020
DOI: 10.3390/ma13163654
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Aggregation of Molecular-Like Fluorophores Driven by Extreme pH in Carbon Dots

Abstract: The origin of carbon-dots (C‑dots) fluorescence and its correlation with the dots structure still lack a comprehensive model. In particular, the core-shell model does not always fit with the experimental results, which, in some cases, suggest a molecular origin of the fluorescence. To gain a better insight, we have studied the response of molecular-like fluorophores contained in the C‑dots at extreme pH conditions. Citric acid and urea have been employed to synthesize blue and green‑emitting C‑dots. They show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, it has been demonstrated that CA and EDA form fluorescent species in the early stages of hydrothermal synthesis and sp 2 domains arise within minutes (Figure g). As shown in Figure h, the UV–vis absorption is characterized by two strong bands at 250 and 350 nm due to π → π* and n → π* of 2-pyridone molecular moieties. , Whether and how the fluorophores interact in the synthesis process of graphitic domains is still unknown since in the process, particularly under critical conditions such as those of solvothermal treatment or pyrolysis, several mechanisms and precursors could be involved.…”
Section: In Silico Methods For Cnd Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been demonstrated that CA and EDA form fluorescent species in the early stages of hydrothermal synthesis and sp 2 domains arise within minutes (Figure g). As shown in Figure h, the UV–vis absorption is characterized by two strong bands at 250 and 350 nm due to π → π* and n → π* of 2-pyridone molecular moieties. , Whether and how the fluorophores interact in the synthesis process of graphitic domains is still unknown since in the process, particularly under critical conditions such as those of solvothermal treatment or pyrolysis, several mechanisms and precursors could be involved.…”
Section: In Silico Methods For Cnd Studiesmentioning
confidence: 99%
“…As shown in Figure 7h, the UV−vis absorption is characterized by two strong bands at 250 and 350 nm due to π → π* and n → π* of 2-pyridone molecular moieties. 395,396 Whether and how the fluorophores interact in the synthesis process of graphitic domains is still unknown since in the process, particularly under critical conditions such as those of solvothermal treatment or pyrolysis, several mechanisms and precursors could be involved. The presence of molecular fluorophores is indirectly demonstrated by comparing the optical properties (UV−vis and fluorescence) of single molecules in solution with the ones in CNDs.…”
Section: Building Cnd Model Structuresmentioning
confidence: 99%
“…CDs made of CA and polyethylenimine (PEI) or 2,3-diaminopyridine (DAP) have shown a reduction of the QYs from ≈ 40-50% to less than 9% when dissolved in an aqueous solution of pH ≈ 1 and to 21% when the pH has been increased to 12 [88]. The peculiar behavior of some CD's fluorophores formed in situ during CDs carbonization, such as citrazinic acid, has also been recently studied at extreme pH conditions [89,90]. The same fluorophores dissolved in solution have also proved to drastically change their optical properties as a function of the concentration undergoing a transition from monomer to dimer [91].…”
Section: External Variables Controlling the Emissionmentioning
confidence: 99%